Comparative genetic analysis of nosocomial methicillin-resistant Staphylococcus aureus populations in Ireland 1971-2004 - Shore, Anna (Trinity College (Dublin, Ireland). School of Dental Science, 2005)
Methicillin-resistant Staphylococcus aureus (MRSA) is the most prevalent pathogen responsible for nosocomial infections worldwide and Ireland has one of the highest rates of nosocomial MRSA infections in Europe. In the past, phenotypic epidemiological typing techniques such as routine antimicrobial susceptibility testing and phage typing, and more recently, pulsed-field gel electrophoresis (PFGE), have been used to monitor the MRSA population in Irish hospitals. The aim of the present study was to perform a comprehensive molecular analysis of an extensive collection of MRSA isolates recovered from patients in Irish hospitals between 1971 and 2004, in order to assess the genetic relationships of nosocomial MRSA in Ireland since its first isolation over thirty years ago. Isolates were also investigated for the prevalence of lysogenic single-, double- and triple- converting serotype F phages, which encode the important virulence factors enterotoxin A (EntA) and staphylokinase (Sak). A combination of multilocus sequence typing (MLST), which determines the genetic background of bacterial isolates and analysis of the staphylococcal chromosomal cassette (SCCmec) element, which carries the genetic determinant for methicillin- resistance mecA, was used in the present study to characterise the MRSA isolates. In addition, PFGE was performed on MRSA isolates collected during a surveillance study in 1999 to examine the relationship between isolates exhibiting a newly recognised phenotype (AR43) and isolates with other phenotypes collected during the same study.
Keywords: Dental Science, Ph.D.; Ph.D. Trinity College Dublin